Rachana Vidhi: Metode Desain Interior Berbasis Budaya Lokal dan Revolusi Industri 4.0 - I Kadek Dwi Noorwatha; Putu Ari Darmastuti; Ni Luh Kadek Resi Kerdiati (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2020)
This research is a fundamental research that seeks to formulate an interior design method based on local culture and the industrial revolution 4.0 called 'Rachana Vidhi'. The research problem arises from the urgent need for the formulation of an ideal interior design method, which combines the development of local culture, the needs of the interior design industry and implements the spirit of the industrial revolution 4.0. The research method uses a qualitative document study approach specifically with the systematic review method, which is combined with the comparative method. The reseach results of the 'Rachana Vidhi' method have been discussed using the basic framework of the stages of the HDII professional organization as a synergy between academics and professional organizations. The method also balances knowledge and abilities between academics and practitioners with the 'research based design' paradigm. In the context of cultural development, the interior design method 'Rachana Vidhi' has been filled in at the ‘Predesain’ stage especially at step no. 15 Cultural Exploration, as part of the drafting of interior design concepts. Synergy with the industrial revolution 4.0 on the interior design method 'Rachana Vidhi' is applied to the stages of Input, Design, Conceptual Design and Design Development. Industrial revolution 4.0 application used is for insight searching, data collecting and modeling.